2020
DOI: 10.3390/membranes10050090
|View full text |Cite
|
Sign up to set email alerts
|

Electroseparation of Slaughterhouse By-Product: Antimicrobial Peptide Enrichment by pH Modification

Abstract: The fractionation of bioactive peptides from hydrolysate is a main challenge to produce efficient alternative for synthetic additives. In this work, electrodialysis with ultrafiltration membrane (EDUF) was proposed to increase the purity of one antimicrobial peptide from slaughterhouse by-product hydrolysate. This targeted-peptide, α137–141 (653 Da, TSKYR), inhibits a large spectrum of microbial growths and delays meat rancidity; therefore, if concentrated, it could be used as food antimicrobial. In this conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…The fraction was obtained at the lowest energy consumption (3.4–5 kWh/kg) when using 5–8% hemoglobin in the initial feed. The good antimicrobial results led them to optimize the process by studying the influence of the degree of hydrolysis (DH) [ 338 ] and the pH [ 339 ]. By targeting TSKYR (α 137–141, 653 Da), an antimicrobial peptide with interesting properties for meat taste preservation, they found that pH 9 increased the purity of the fraction, while a 5% DH allowed a 13-fold concentration of TSKYR compared to the initial hydrolysate.…”
Section: Integration Of Ed Technologies In New Sustainable Strategmentioning
confidence: 99%
“…The fraction was obtained at the lowest energy consumption (3.4–5 kWh/kg) when using 5–8% hemoglobin in the initial feed. The good antimicrobial results led them to optimize the process by studying the influence of the degree of hydrolysis (DH) [ 338 ] and the pH [ 339 ]. By targeting TSKYR (α 137–141, 653 Da), an antimicrobial peptide with interesting properties for meat taste preservation, they found that pH 9 increased the purity of the fraction, while a 5% DH allowed a 13-fold concentration of TSKYR compared to the initial hydrolysate.…”
Section: Integration Of Ed Technologies In New Sustainable Strategmentioning
confidence: 99%
“…Using electrolysis aided membrane technology, Przybylski et al 111 recovered a peptide fraction containing more than 50% of the ⊍137-141 peptide from slaughterhouse by-product hydrolysate. Such a bioactive peptide has antibacterial activity against several pathogenic bacteria that cause food spoilage.…”
Section: Recovery Of Protein-based Compounds From Meat Co-products By Electrodialysis With Uf Membranesmentioning
confidence: 99%
“…Using electrolysis aided membrane technology, Przybylski et al 111 . recovered a peptide fraction containing more than 50% of the α137‐141 peptide from slaughterhouse by‐product hydrolysate.…”
Section: Recovery Of Protein‐based Compounds From Meat Co‐products By Electrodialysis With Uf Membranesmentioning
confidence: 99%
“…The resultant peptide concentration had 50% of α137-141 in it. Have this peptide concentrate can also be used as a natural preservative alternatively do synthetic additives (Przybylski et al, 2020).…”
Section: Meat Industrymentioning
confidence: 99%